Programa de juegos recreativos tradicionales para mejorar el pensamiento creativo en estudiantes de la carrera de Educación Inicial de la Facultad de Educación UNAP 2025 - Cuipal Torres, Julio Segundo (2025)
This study aimed to “determine the effect of a traditional recreational games program on the improvement of creative thinking in students of the Early Childhood Education program at the Faculty of Education, UNAP – 2025”. The research followed a quantitative approach with a quasi-experimental design, using a pretest and posttest applied to a single experimental group composed of higher education students. The creative thinking dimensions—fluency, flexibility, originality, and elaboration—were evaluated using a validated rubric. The results showed significant improvements after the intervention: the percentage of students at the "excellent" level in overall creative thinking increased from 7.4% to 74.1%, while the "deficient" and "regular" levels decreased notably. Specifically, all dimensions showed considerable increases at the "excellent" level, particularly originality (from 51.9% to 81.5%) and elaboration (from 33.3% to 77.8%). It is concluded that the traditional recreational games program had a positive impact on the development of creative thinking across its various dimensions. The use of culturally based playful strategies fostered meaningful, participatory, and stimulating learning, which is essential in the training of future educators.